Electrical and thermal transport properties of Nb- and Ru-substituted Mo3Al2C superconducting compounds. (22nd January 2016) - Ramachandran, B; Jhiang, J Y; Kuo, Y K; Kuo, C N; Lue, C S
Abstract: Partial substitution effects of Nb and Ru on the superconducting and normal-state properties of Mo3 Al2 C-based compounds, namely Mo3− x Nb x Al2 C ( x  = 0.00–0.25) and Mo3− x Ru x Al2 C ( x  = 0.00–0.15), were investigated by means of electrical, magnetic, and thermoelectric studies. From the resistivity and magnetization data, we noted that the superconducting transition temperature of Mo3 Al2 C decreases gradually with increasing the dopant content of Nb and Ru, and the superconducting volume fraction also decreases significantly upon the substitution. The electrons dominate the thermoelectric transport in the studied compounds. Moreover, a change of curvature near 50 K in the transport properties of the parent Mo3 Al2 C compound was observed, prior to the superconducting transition. This is most likely due to the strong electron–phonon interaction which could have originated from the distortions near the Al sites. Finally, it was found that electronic carriers contribute considerably to heat conduction of the Mo3 Al2 C-based compounds near room temperature, whereas the phonons dominate the low-temperature thermal transport.